Education Game to Blind People - Sakti, Lidya Oktorina Kusuma; Febriani, Vania Wahyu (Soegijapranata Catholic University, 2015)
Blind people have limitations because of partial or full visual impairment. This can affect their development like cognitive development and academic development. In order to do their social roles, blind people have obstacles. Even in education side, blind people still find it difficult to get their full access to study because their physic limitation makes them difficult to study like normal people.Now there are blind people who have their formal and informal education. Even though they cannot see, they can take benefit from another sense, like sense of hearing, palpability, smell, and taste. Their senses can be a modal to study. Developer games have their build game in audio to blind people too. Their game is variation between audio games and online games, so games can be used for blind people as an education tools. In this paper, there will be an explanation about how to facilitate blind people to study with paper